THE CORRELATION BETWEEN ACADEMIC STRESS AND ACADEMIC MOTIVATION IN FIRST-YEAR NURSING STUDENTS - Sohndic Christino; Neva Cahyani Telambanua; Hedena Tabitha Purba; Ineke Patrisia; Santa Maya Pramusita (Nursing Current: Jurnal Keperawatan, 2024)
Academic stress is a common phenomenon in academic environments, particularly among first-year students. Several students have reported that academic stress can influence their learning motivation, as evidenced by findings from this study. This research aims to examine the relationship between academic stress and academic motivation among first-year nursing students at a private university in Indonesia. A non-experimental quantitative research method with a cross-sectional approach was employed. The study population consisted of 419 first-year nursing students, with a sample size of 205 students selected through simple random sampling. The research instruments included the Educational Stress Scale for Adolescents (ESSA) by Sun et al. (2011) and the Academic Motivation Scale (AMS) by Vallerand et al. (1992). The ESSA instrument demonstrated high validity and reliability, with a Cronbach's Alpha of 0.932. The AMS questionnaire, validated and adapted into Indonesian by Natalya (2018), assessed intrinsic and extrinsic motivation as well as amotivation, showing robust psychometric properties (RMSEA ≤ 0.08; GFI ≥ 0.9; CR ≥ 0.7; α ≥ 0.7). Data analysis utilized Pearson correlation tests, revealing a significant relationship between academic stress and academic motivation (p = 0.001, p < 0.05). The findings indicate that increased academic stress can enhance academic motivation, highlighting the concept of positive stress (eustress). Future studies are encouraged to design interventions aimed at helping students balance academic stress and motivation using experimental methods.